2014
DOI: 10.1021/ja503360y
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Diffraction Study of Catalytic Hydrogenation of VO2: Stable Phases and Origins of Metallicity

Abstract: Controlling electronic population through chemical doping is one way to tip the balance between competing phases in materials with strong electronic correlations. Vanadium dioxide exhibits a first-order phase transition at around 338 K between a high-temperature, tetragonal, metallic state (T) and a low-temperature, monoclinic, insulating state (M1), driven by electron-electron and electron-lattice interactions. Intercalation of VO2 with atomic hydrogen has been demonstrated, with evidence that this doping sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
110
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(115 citation statements)
references
References 26 publications
(41 reference statements)
5
110
0
Order By: Relevance
“…It effectively increases the electronegativity of O p in Ir-O p bond, thereby making the Ir-O p bond ionic. Similar mechanism but opposite trend has been discussed in H doped VO 2 30. The enhanced ionic character of the Ir-O p bond can decrease hybridisation between two ions.…”
Section: Discussionsupporting
confidence: 68%
“…It effectively increases the electronegativity of O p in Ir-O p bond, thereby making the Ir-O p bond ionic. Similar mechanism but opposite trend has been discussed in H doped VO 2 30. The enhanced ionic character of the Ir-O p bond can decrease hybridisation between two ions.…”
Section: Discussionsupporting
confidence: 68%
“…It is reported that hydrogen incorporated into M-VO 2 crystals can stabilize the metallic VO 2 phase at room temperature [10][11][12][13][14] and further lead to an insulating phase in the high doping regime [15]. Explained in the context of crystal-field theory [16,17], the H-doping induced band structure evolutions is represented in Fig.…”
mentioning
confidence: 99%
“…Of the prototypical materials, VO 2 is promising as it undergoes a metal-insulator transition (MIT) and the resistance changes by orders of magnitude around 340 K. In VO 2 nano to microstructures5678910111213, the coupling of the MIT with mechanical789, optical13, thermal12 and electronic properties911 can be used in tunable resonators, optical switchers, electronic and thermo-sensing devices. Furthermore, only a few atomic percent of the hydrogen- or oxygen-intercalation and -desorption in VO 2 cause drastic changes in the transport properties, equal to that caused by inducing the MIT14151617181920. Conventionally, controlling the amount of hydrogen/oxygen ions in an oxide has been conducted by annealing the samples under redox gas atmospheres141516, in an aqueous solution1718 and with a hydrogen spillover method1419.…”
mentioning
confidence: 99%